EFFECT OF PSYCHOEDUCATION ON THE LEVEL OF ACADEMIC STRESS IN IMPROVING COPING STRATEGIES OF FINAL STUDENTS - Purnomo; Anggraini, Ria; Suciati, Suciati; Herminaju, Ketjuk; Fayakun, Fayakun; Nurhidayati, Nurhidayati; Maksum, Maksum (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Students are a special group of individuals involved in tertiary education. Final-year students experience higher academic stress due to thesis, time pressure, and transition to professional life. Through the learning process, students will encounter and overcome obstacles in their educational journey. Other triggers of student stress include academic pressure, social challenges, family tensions, and financial problems. These conditions cause stress in their lives. Method: Respondents in this study were 112 students in a control group consisting of 56 respondents and an intervention group consisting of 56 respondents. The questionnaire by the Depression, Anxiety, Stress Scale (DASS) consisted of 42 statements. Research design was Quasi-Experimental with a Control Group, Pre-Post Test design with Psychoeducation intervention. Sampling technique by total sampling. Inclusion and exclusion criteria were willing respondents for this study. Result: Stress level on Final Year students in the control group pre-test and post-test results p-value is 0.567 > 0.05, indicating that the control group isn’t affected before and after intervention. And then on the intervention group pre-test and post-test intervention, results are p = Value is 0.004 < 0.005, concluding that the intervention group pre-test and post-test intervention significantly affected stress levels in final students. Conclusion: Psychoeducation is one strategy for handling academic stress, which can be applied in individual, family, and group settings, focusing on psychological education of participants regarding various problems faced in life, helping people to develop supportive environments, and developing coping skills to manage various problems.